THE EFFECT OF ILLEGAL PARKING ON TRAFFIC CONGESTION ALONG BARANGAY 176 CALOOCAN CITY (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Urbanization is a worldwide occurrence, and alongside it arises a variety of difficulties that impact the everyday existence of urban inhabitants (Kuddus, et. al., 2020). One of the issues that affects urban regions globally is traffic congestion. Traffic congestion is a complex dilemma stemming from a mix of factors, such as population increase, rising vehicle ownership, insufficient transportation infrastructure, and, most critically, unlawful parking. In Barangay 176, Caloocan City, these difficulties are intensified due to its position within the heavily urbanized Metro Manila area, where traffic congestion remains an ongoing concern. The descriptive research method is relevant for this study aimed at recording and describing various facets of illegal parking and its impact on traffic congestion in Barangay 176, Caloocan City. Regarding Traffic Congestion, respondents expressed strong agreement that vehicles parked illegally significantly deteriorated traffic flow. Concerning Pedestrian Obstruction, respondents strongly concurred that illegally parked vehicles often impeded pedestrian movement on sidewalks. With respect to Travel Time Delays, respondents widely agreed on the importance of tackling illegal parking to reduce delays for both private and public transportation. In improving enforcement and penalties, boost the amount of traffic enforcers present to more effectively observe and prevent unauthorized parking. Furthermore, to promote compliance with parking regulations, think about raising the fines for penalties and infractions. In upgrading parking infrastructure, enhance existing parking facilities and offer additional off-street parking spaces, as well as develop plans for zones designated for loading and unloading to alleviate traffic congestion. Initiate public awareness campaigns to educate drivers and passengers regarding the repercussions of illegal parking. This might also involve motivating community members to actively participate in these awareness initiatives. Think about creating longitudinal studies to evaluate the long-term effectiveness of various strategies that could potentially reduce traffic congestion and dissuade unauthorized parking. Investigate other elements such as cultural backgrounds and socioeconomic conditions that could influence compliance with parking regulations.
Keywords: traffic congestion; illegal parking; pedestrian obstruction; travel time delays